Posted by **Melinda** on Monday, January 30, 2012 at 5:43pm.

log(base2)x-log(base2)6= log(base2)5+ 2log(base2)3

log(x/6)=3log15

(x/6)=15^3

6*(x/6)=15^3*6

x=15^3*6

=20,250

Answer is 270....

What did I do wrong...

## Answer this Question

## Related Questions

- Algebra - In the logarithmic expression . . . log(base 4) 8 , how does the base ...
- Calculus - I have trouble finding the second derivative, my answer is a little ...
- Algebra 2 - How would I solve the equation: log(base2)4 - log(base2)(x+3) = log(...
- Calculus - Find the second derivative of the following function: y=log(base2)x/x...
- Algebra 2 - solve the equation: log(base2)^(x-3)log(base2)^5 = 2log(base2)^10 I ...
- math - Given that 2 log base2 (x+15) - log base2 x = 6 1.Show that x^2 -34x +225...
- Math 12 - 7. Simplify. b) log base2 20 + log base3 8 + log base2 3 + log base3 4...
- Advanced Functions/ Precalculus Log - 1. Evaluate 4^(log base4 64) + 10^(log100...
- Math - Evaluate log(base2)8-log(base2)12+log(base2)6
- Pre-Cal - log base2 5 square root of 512 use the definition of b^1/n log base2 ...

More Related Questions